Reality check teenage fathers speak out - Trapani, Margi (New York The Rosen Pub. Group, 1997)
Teenage fathers highlight the challenges of being a teen parent, discussing responsibility, economic hardship, and emotional issues involved in parenting at a young age.
Includes bibliographical references (p. 61-62) and index.
Keywords: Teenage fathers -- United States -- Case studies -- Juvenile literature; Teenage pregnancy -- United States -- Case studies -- Juvenile literature; Parenting